Creación de muros de uso libre para promover el empoderamiento artístico en los estudiantes de la carrera de Pedagogía de las Artes y Humanidades de la Universidad Nacional de Chimborazo. - Arguello Tacuri, Emilio Santiago (2024)
The creation of free-use walls in universities is not merely an artistic manifestation; it becomes a powerful tool to foster a sense of belonging and motivation among students and the community. This study focused on designing a free-use wall aimed at artistically empowering students in the Pedagogy of Arts and Humanities program at the National University of Chimborazo (UNACH). Through a qualitative approach, the research explored how students participate in this project and its impact on their personal and academic development. The descriptive and exploratory study centered on the wall implemented in July 2024 on the La Dolorosa campus. The findings revealed that students feel a pressing need for spaces where they can express themselves artistically and freely, as the lack of such spaces has limited their creative growth and ability to experiment with various techniques and visual styles. Thus, the free-use wall emerges as a response to this demand, providing a platform that promotes self-expression and the development of essential artistic skills. Ultimately, this initiative not only enhances the individual development of students but also contributes to creating a better learning environment